αII-Spectrin Regulates Invadosome Stability and Extracellular Matrix Degradation - Ponceau, Aurélie (PLoS One, 2015)
Invadosomes are actin-rich adhesion structures involved in tissue invasion and extracellular matrix (ECM) remodelling. αII-Spectrin, an ubiquitous scaffolding component of the membrane skeleton and a partner of actin regulators (ABI1, VASP and WASL), accumulates highly and specifically in the invadosomes of multiple cell types, such as mouse embryonic fibroblasts (MEFs) expressing SrcY527F, the constitutively active form of Src or activated HMEC-1 endothelial cells. FRAP and live-imaging analysis revealed that αII-spectrin is a highly dynamic component of invadosomes as actin present in the structures core. Knockdown of αII-spectrin expression destabilizes invadosomes and reduces the ability of the remaining invadosomes to digest the ECM and to promote invasion. The ECM degradation defect observed in spectrin-depleted-cells is associated with highly dynamic and unstable invadosome rings. Moreover, FRAP measurement showed the specific involvement of αII-spectrin in the regulation of the mobile/immobile β3-integrin ratio in invadosomes. Our findings suggest that spectrin could regulate invadosome function and maturation by modulating integrin mobility in the membrane, allowing the normal processes of adhesion, invasion and matrix degradation. Altogether, these data highlight a new function for spectrins in the stability of invadosomes and the coupling between actin regulation and ECM degradation.